Strain-induced variation of bandgap in (111) In2O3 epitaxial films grown on c-sapphire substrates by a pulsed laser deposition technique. (4th February 2021) - Yadav, Santosh Kumar; Arora, Simran; Dhar, Subhabrata
Abstract: The structural and electronic properties of In2 O3 epitaxial films grown on c-sapphire substrates by a pulsed laser deposition technique are studied as functions of various growth conditions. Our study shows that growth temperature, growth time, oxygen partial pressure, and post-growth cooling conditions play important roles in governing the magnitude and character of the overall change in unit cell volume (volume strain) of the lattice. It is found that biaxial strain, which is developed due to lattice and thermal expansion coefficient mismatches between the layer and the substrate, leads to overall compression of the lattice. Interestingly, a hydrostatic tensile strain is found to coexist with biaxial strain in samples, which, following growth, are cooled to room temperature at a rate much slower than the natural rate of cooling. It has been observed that the overall strain can be varied from compressive to tensile by changing the growth parameters. The study further shows a systematic variation of the bandgap (from 3.8 to 3.1 eV) with a change in the unit cell volume of these layers, demonstrating the strong influence of strain on the band structural properties of the material.